Requirements for development of cMOOC platforms from the professional's perspective - Venega, Virginia de S.; Maciel, Rita Suzana Pitangueira (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2021)
MOOC with a Connectivist approach (cMOOC) are heavily dependent on peer collaboration for knowledge construction. Requirements for elicitation for these environments are not a trivial task and should take different perspectives. This paper describes a study carried out with informatics and education professionals to identify the software requirements to compose cMOOC platforms. In this context, a questionnaire was applied and, after analysis, returned 116 requirements divided into 11 categories, coded in correlation with the four dimensions of connectivism. In the future, it is expected with this research to compose requirements catalogue to contribute to software development in cMOOC domain.